The impact of acupuncture on neuroplasticity after ischemic stroke: a literature review and perspectives - Qin, Siru; Zhang, Zichen; Zhao, Yadan; Liu, Jingyi; Qiu, Jiwen; Gong, Yinan; Fan, Wen; Guo, Yongming; Guo, Yi; Xu, Zhifang; Guo, Yang (Frontiers in Cellular Neuroscience, 2022)
Ischemic stroke is common in the elderly, and it is one of the main causes of long-term disability worldwide. After ischemic stroke, spontaneous recovery and functional reconstruction take place. These processes are possible thanks to neuroplasticity, which involves neurogenesis, synaptogenesis, and angiogenesis. However, the repair of ischemic damage is not incomplete, and neurological deficits develop eventually. The WHO recommends acupuncture as an alternative and complementary method for the treatment of stroke. Moreover, clinical and experimental evidence has documented the potential of acupuncture to ameliorate ischemic stroke-induced neurological deficits, particularly sequelaes such as dyskinesia, spasticity, cognitive impairment, and dysphagia. These effects is related to the ability of acupuncture to promote spontaneous neuroplasticity after ischemic stroke. Specifically, acupuncture can stimulate neurogenesis, activate axon regeneration and sprouting, and improve the structure and function of synapses. These processes modify the neural network and function of the damaged brain area, producing the improvement of various skills and adaptability. Astrocytes and microglia may be involved in the regulation of acupuncture on neuroplasticity, such as the production and release of a variety of neurotrophic factors, including brain-derived neurotrophic factor (BDNF), nerve growth factor (NGF), neurotrophin-3 (NT-3), etc. Moreover, the presented evidence confirms that the functional reconstruction of the whole brain after ischemia plays an important role in the process of acupuncture regulating neuroplasticity. Therefore, neuroplasticity is expected to become a new target for acupuncture in the treatment of neurological deficits after ischemic stroke, and it is of great clinical value to conduct in-depth research and excavation on it.